Giant Condyloma of Bushke-Löwenstein (GCBL) in Pregnancy: A Case Report - Delgado Macías, Priscila; Varela Barraza, Omar; Sánchez Terán, Alfonso Iván; Germes Piña, Fernando; Macías Grageda, Michelle Alejandra; Luévano González, Arturo (International Journal of Innovative Research in Medical Science, 2023)
We present a case of Giant condyloma of Bushke-Löwenstein (GCBL) in a 15-year-old pregnant woman from the Tarahumara ethnic group. GCBL is a rare sexually transmitted disease caused by the the Human Papillomavirus (HPV) with a high risk of malignant transformation. Surgical resection is the main treatment, but managing GCBL during pregnancy requires careful consideration. This case highlights a rare and challenging condition that shares features with both classic condyloma acuminata and squamous cell carcinoma, making its differentiation difficult and the importance of comprehensive sexual education, culturally sensitive healthcare, and follow-up care in underserved communities. Challenges in post-surgical monitoring and limited knowledge of perinatal outcomes underscore the need for increased awareness, prevention, and early detection strategies, including HPV vaccination.